Efektivitas dan Dampak Program SPP Terhadap Pendapatan dan Jam Kerja Anggota Kelompok SPP di Kecamatan Sukawati Kabupaten Gianyar - Kusmeiran, Yan Handrey; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
PNPM Mandiri since it launched until now can be considered the most preferred program in the development process. Gender equality, empowerment of the poor and increased community participation is one of the added value in this program. One of the superior programs of the PNPM Mandiri is Program of Simpan Pinjam Perempuan (SPP) . As one of the government programs, the SPP Program is supposed to be evaluated to determine whether these programs have a positive impact on the welfare of the community or not . The purpose of this study was to determine the level of effectiveness of the SPP program in the District of Sukawati, in terms of the stages of planning, implementation and sustainability program. This study also aims to determine the impact of the SPP Program on the level of income and the rate of flow of the household working hours SPP members, as well as to determine the public perception and PNPM’s actors, especially in the SPP program in the District of Sukawati. The method used to determine the level of effectiveness of the SPP program is descriptive method of analysis techniques which adopt the method of measurement of Community Satisfaction Index (HPI) Service Unit of Government Agencies. To determine the impact of the SPP Program on the level of income and the rate of flow of household work hours SPP members, conducted Paired-Sample T test. As for knowing people's perceptions and PNPM’s actors conducted by descriptive statistic with questionnaire and structured interviews. The data used in this study is primary data obtained from questionnaires distributed to members of the SPP as the object of this study. The results showed that the level of effectiveness of the implementation of the SPP program in the District of Sukawati quite effective, with a value of 77.80 percent. SPP program is also a significant impact on revenue growth and an outpouring of household work hours SPP members. Besides, the public and the perpetrators of these activities provide a very positive appreciation for this program. The conclusion that can be drawn from this study is that the PNPM program is a breakthrough that is fairly successful in the eyes of society. It is therefore recommended that the sustainability of this program be maintained and guaranteed by the government, and the SPP groups already formed continue to be fostered in order to remain productive and able to contribute positively to the welfare of society in general.
Keywords: Poverty; Gender Equality; Empowerment